Theology after postmodernity : divining the void--a Lacanian reading of Thomas Aquinas - Beattie, Tina (Oxford University Press, 2013)
Theology after Postmodernity is a ground-breaking study that has the capacity to transform the relationship between psychoanalytic theory and Christian theology. Reading the theology of Thomas Aquinas in close engagement with the psychoanalytic theory of Jacques Lacan, Tina Beattie shows how Thomism exerted a formative influence on Lacan, and she also shows how a Lacanian approach can bring rich new insights to Thomas's theology.